The European Union’s interregionalism in the Andean Community - Andree Juvenal Jimenez Soto; Julio Ricardo Moscoso Cuaresma; Raúl Alejandro Quispe Medina; Andy Roli Fernandez Lerzundi; Elizabeth Melissa Céspedes Orrego; Kristina Alexandra Miyashiro Oshiro (Cogent Social Sciences)
This article examines the impact of EU interregionalism on regional integration in the Andean Community. The study employs a qualitative approach based on theoretical literature and economic data to examine the impact of EU interregional strategies in the Andean Community, both politically and economically. The article identifies that, despite the EU’s initial efforts to consolidate inter-bloc relations, the internal divisions within the Andean Community and the global competition and influence of external actors such as China and the United States have led Europeans to focus predominantly on bilateral agreements with the Andean countries of the Andean Community. This study also contributes to the academic debate by providing a detailed analysis of the limitations and opportunities of EU-Andean Community relations, and by highlighting the role of interregionalism in the evolution of regional integration models in Latin America.